Drying Of Sliced Materials Under The Influence Of Ultrasonic And Infrared Radiations - Low, Hua Chin (2011)

(untitled)
Convective drying has been commonly used in preservation of the agricultural products. The respective drying rates generally depend on the effective diffusion coefficients of moisture within the materials. Increase in ultrasonic power and frequency as well as infrared power have been found to enhance the· convective drying process rates. The main aim of this work is to study the influence of the ultrasonic frequency and infrared power on the effective diffusion coefficients of. ~oisture ~thin the materia~s. Pengeringan olakan biasanya digunakan dalam pengawetan produk pertanian. Kadar pengeringan secara umumnya bergantung kepada pekali resapan kelembapan berkesan dalam bahan-bahan. Penambahan kuasa dan frekuensi ultrasonik dan inframerah telah diketahui boleh meningkatkan kadar proses pengeringan olakan. Objektif utama bagi kajian ini adalah untuk mengkaji pengaruh frekuensi ultrasoriik dan kuasa inframerah kepada pekali resapan berkesan bagi kelembapan dalam bahanbahan.